Lack of Association between the Platelet Glycoprotein Ia C807T Gene Polymorphism and Myocardial Infarction in Japanese - Morita, Hiroyuki; Kurihara, Hiroki; Imai, Yasushi; Sugiyama, Takao; Hamada, Chikuma; Sakai, Eiichi; Mori, Mitsuko; Nagai, Ryozo (Thrombosis and Haemostasis, 2001)
The platelet-collagen receptor, glycoprotein Ia/IIa (integrin α2β1) plays a fundamental role in the adhesion of platelets to fibrillar collagen, an event leading to platelet activation and thrombus formation and contributing to the pathogenesis of thrombotic disease. Further, glyco-protein Ia/IIa receptor density and function may be associated with two linked and silent polymorphisms (807C/T and 873G/A) within the glyco-protein Ia gene. We tested the extent to which these polymorphisms serve as genetic markers of myocardial infarction in a Japanese population. A case-control study was carried out using 210 Japanese myocar-dial infarction patients and 420 age- and sex-matched controls. Geno-typing was accomplished using PCR followed by melting curve analysis with specific fluorescent hybridization probes. The 807CC, CT, TT genotypes linked perfectly to the 873GG, GA, AA genotypes, respectively. Allele frequencies of the 807T (873A) variant were similar in the control and patient groups (0.373 vs. 0.352). The 807T and 873A variants of platelet glycoprotein Ia gene are common and in a perfect linkage in the Japanese population, but it appears unlikely that the 807T (873A) variant represents a useful marker of increased risk for myocardial infarction.
Keywords: Platelet glycoprotein; myocardial infarction; melting curve analysis; genetics; ethnic difference